Dc Conductance and Memory in 3d Gravity - Pino-Rozas, M; Lara-Díaz, K; Cardenas-Lisperguer, M (Springer Science and Business Media Deutschland GmbH, 2022)
Transport properties are investigated in the two-dimensional dual dynamics of AdS3 gravity. By providing boundary conditions that deform the ADM lapse and shift functions, we construct a lower dimensional model comprising two copies of chiral boson excitations with anisotropic scaling symmetry. Using bosonization, an electric current is identified. By means of the Kubo formula, we find a DC conductance depending on the level of the theory and the dynamical exponents. The bulk realization of the linear response is related to a type of gravitational memory emerging in the context of near-horizon boundary conditions. The process is adiabatic and represents a permanent spacetime deformation parametrized by anisotropic chiral bosons through a large gauge transformation. © 2022, The Author(s).
Keywords: Classical Theories of Gravity; Global Symmetries; Chern-Simons Theories; Field Theories in Lower Dimensions